Collagen coated electrospun polyethersulfon nanofibers improved insulin producing cells differentiation potential of human induced pluripotent stem cells. (12th November 2018) - Mansour, Reyhaneh Nassiri; Soleimanifar, Fatemeh; Abazari, Mohamad Foad; Torabinejad, Sepehr; Ardeshirylajimi, Abdolreza; Ghoraeian, Pegah; Mousavi, Seyed Ahmad; Sharif Rahmani, Edris; Hassannia, Hadi; Enderami, Seyed Ehsan
Abstract: Given the current conditions of life, one of the problems that the world is facing and is rapidly expanding is diabetes. The existing treatment methods are not responsive to these patients. Today, due to the advent of tissue engineering, cell and stem cell therapies, there are many hopes for treating these patients. In the present study, Polyethersulfone (PES) nanofibers were fabricated by electrospinning and then coated by collagen (PES-collagen), since this protein is abundant at the pancreatic extracellular matrix. After scaffold characterization, pancreatic differentiation potential of human induced pluripotent stem cells (hiPSCs) was investigated when cultured on PES-collagen by RT-qPCR, Immunofluorescence staining and insulin and C-peptide release assays. Pancreatic genes and proteins in cultured iPSCs on PES-collagen were expressed significantly higher than those cultured on culture plate as 2 D control group. Although differentiated cells in both groups are functional and secrete C-peptide and insulin in response to glucose challenges according to the immunoassay result. Considered together, PES-collagen demonstrated that it can be effective during pancreatic differentiation of the stem cells and can also be considered as a promising candidate for use in pancreatic tissue engineering application.